Principio de contradicción en audiencias telemáticas - Orellana Batallas, Fabian (2023)
In the year 2020, the world will experience a series of massive infections caused by COVID 19. Different restrictions will be determined in all fields of social life, such as in the judicial system; For this reason, the National Court of Justice of Ecuador established a protocol for conducting the telematic hearing. However, despite the progress, concern arises by not addressing issues that could affect the procedural principles that revolve around the principle of innocence, such as that of contradiction; For this reason, the descriptive investigative provenance is to show how the lack of regulations that regulate telematic hearings in Ecuador can cause the judge to receive unclear information. This type of analysis with a qualitative approach based on theoretical and empirical methods allows us to identify in the study how a biased perception is triggered in terms of the information provided by the participants in a hearing, since witnesses, experts and other professionals participate in it. That provide elements for the judge to create a sound judgment at the time of solving, observing itself as a solution to the problem.